The Effect of Service Quality Elements on Customer Satisfaction - B. Bungatang; R. Reynel (Golden Ratio of Marketing and Applied Psychology of Business, 2021)
The research objective was to determine and analyze the influence of the physical evidence of service quality, caring, responsiveness, reliability, and guaranteeing customer satisfaction at the PT. Pegadaian Watansoppeng branch. Research carried out explanatory research and survey methods. The study population is new clients served PT. Pegadaian Watansoppeng Branch Company. The samples were taken using purposive sampling and obtained 100 samples. This research's data analysis methods are descriptive analysis with Linear Regression calculation, where the independent variables consist of physical evidence, concern, responsibility, reliability, assurance, dependent variable satisfaction customer. The results of studies using multiple linear regression analysis showed that service quality dimensions significantly influence customer satisfaction. As for the t-test is known that a significant level for each variable that is physical evidence = 0.658, concern = 0.002, responsiveness = 0.338, reliability = 0.000, and assurance = 1.239. From these results, two variables can prove the second hypothesis suggesting that the physical evidence of service quality dimensions, concern, responsiveness, reliability, and guarantees the dominant influence on customer satisfaction at the PT. Pegadaian Watansoppeng branch of the variable of concern and reliability and three other variables that physical evidence, responsiveness, and assurance are support for this study hypothesis.